Palmitic acid induces inflammatory cytokines and regulates tRNA-derived stress-induced RNAs in human trophoblasts - Changwon Yang; Garam An; Jisoo Song; Gwonhwa Song; Whasun Lim (The Korean Society of Animal Reproduction and Biotechnology, 2022)
High levels of proinflammatory cytokines have been observed in obese pregnancies. Obesity during pregnancy may increase the risk of various pregnancyrelated complications, with pathogenesis resulting from excessive inflammation. Palmitic acid (PA) is a saturated fatty acid that circulates in high levels in obese women. In our previous study, we found that PA inhibited the proliferation of trophoblasts developing into the placenta, induced apoptosis, and regulated the number of cleaved halves derived from transfer RNAs (tRNAs). However, it is not known how the expression of tRNA-derived stress-induced RNAs (tiRNAs) changes in response to PA treatment at concentrations that induce inflammation in human trophoblasts. We selected concentrations that did not affect cell viability after dose-dependent treatment of HTR8/SVneo cells, a human trophoblast cell line. PA (200 μM) did not affect the expression of apoptotic proteins in HTR8/SVneo cells. PA significantly increased the expression of inflammatory cytokines including interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor (TNF)-α. In addition, 200 μM PA significantly increased the expression of tiRNAs compared to 800 μM PA treatment. These results suggest that PA impairs placental development during early pregnancy by inducing an inflammatory response in human trophoblasts. In addition, this study provides a basis for further research on the association between PA-induced inflammation and tiRNA generation.